2001
DOI: 10.1111/j.1469-7793.2001.0065b.x
|View full text |Cite
|
Sign up to set email alerts
|

Pharmacological aids to locomotor training after spinal injury in the cat

Abstract: This Topical Review summarizes some of the work we have done mainly in the cat using agonists and antagonists of various neurotransmitter systems injected intravenously or intrathecally to initiate or modulate the expression of hindlimb locomotion after a spinal lesion at T13. The effects of the same drugs are compared in various preparations: complete spinal, partial spinal or intact cats. This has revealed that there can be major differences in these effects. In turn, this suggests that although the locomoto… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
79
0
11

Year Published

2004
2004
2019
2019

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 106 publications
(91 citation statements)
references
References 61 publications
1
79
0
11
Order By: Relevance
“…If so, attempts to substitute this supraspinal drive in spinal subjects by pharmacological or electrical stimulation of the cord below the lesion seem plausible. These methods appeared efficient for restoration of locomotor function in spinal animals (e.g., Gerasimenko et al 2008;Musienko et al 2007;Rossignol et al 1998Rossignol et al , 2001.…”
Section: Spinal Versus Supraspinal Origin Of Postural Responsesmentioning
confidence: 99%
“…If so, attempts to substitute this supraspinal drive in spinal subjects by pharmacological or electrical stimulation of the cord below the lesion seem plausible. These methods appeared efficient for restoration of locomotor function in spinal animals (e.g., Gerasimenko et al 2008;Musienko et al 2007;Rossignol et al 1998Rossignol et al , 2001.…”
Section: Spinal Versus Supraspinal Origin Of Postural Responsesmentioning
confidence: 99%
“…This approach was successfully used for activation of the hindlimb locomotor CPGs (Rossignol et al 1998(Rossignol et al , 2001. It was also shown that the two approaches (electrical and pharmacological stimulation) could be combined to enable well-coordinated stepping (Courtine et al 2009;Gerasimenko et al 2007).…”
Section: Introductionmentioning
confidence: 99%
“…1,2 In fact, even without pharmacological aids, regular TT assisted with a weight-supporting harness and/or tail or sexual organ pinching can enable the expression of involuntary 'reflex' stepping in low-thoracically spinal cord-transected (Tx) animals. [3][4][5] However, without assisted training, some spontaneously occurring small amplitude hindlimb movements were also shown to progressively occur a few weeks post-Tx in untrained Tx mice, [6][7][8] suggesting that basic spontaneous sublesional plasticity and spinal learning events may occur even in the absence of assisted training.…”
Section: Introductionmentioning
confidence: 99%